Jokes are not Innocent: Representation of Punjabis in Pashto Jokes - Muhammad Waqar Ali (University of Chitral Journal of Linguistics and Literature)
In this paper, the researcher analysed racist or ethnic jokes as a genre of discourse to investigate the issue of representation of Punjabis in Pashto jokes. The emphasis of the paper was on understanding stereotypes and symbols associated with the representation of Punjabis in Pashto jokes. The data for the study comprised oral jokes of Pakhtuns from Peshawar. The researcher followed John stone (2008) and Linde (1993) for discourse analysis of the jokes. Further, the researcherfollowed Althusser (1971) as theoretical framework to explain the reason(s) behind the way Pakhtuns present Punjabis in their jokes. At the end, the researcher concluded that ideology through cultural Ideological State Apparatus interpellates (i.e. calls out or hails) Pakhtuns as subjects.